Analysis of Business Center Implementation in Banyumas Regency - Naufalin, Lina Rifda; Dinanti, Aldila; Krisnaresanti, Aldila (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
The research aims to help the development of business center as an entrepreneurship laboratory for vocational students in order to increase the number of young entrepreneurs in Indonesia. This study is also Â to find out how the implementation of the existing Business Center program in SMK Banyumas District viewed from the aspects of learning, economics, organizational, and capital. Research method used qualitative method and techniques of collecting data used observation and interview. The place of research is in Vocational School 1 Purwokerto and Vocational School 2 Purwokerto. The sampling technique was purposive sampling technique. Validity of data in this research used data triangulation.The result of the research shows that the learning aspect of the implementation of the business center is effective because it becomes the student training center. Economic aspect of the business center is effective to carry out the activities of selling goods, goods production and service, business because it is supported by qualified human resources and internal audits conducted regularly. The aspect of the capital of the business center can be managed effectively.